Rehabilitation in subjects with frozen shoulder: a survey of current (2023) clinical practice of Italian physiotherapists - Fabrizio Brindisino; Giuseppe Girardi; Mauro Crestani; Raffaele Assenza; Arianna Andriesse; Giuseppe Giovannico; Leonardo Pellicciari; Mattia Salomon; Davide Venturin (BMC Musculoskeletal Disorders, 2024)
Abstract Objective Frozen Shoulder (FS) is a musculoskeletal pathology that leads to disability, functional decline, and a worsening in quality of life. Physiotherapists are the primary professionals involved in the treatment of FS, and it is essential to determine if their practice aligns with evidence-based suggestions. Aim The aim is to assess the knowledge, skills, and operational strategies of Italian physiotherapists regarding FS and compare them with the existing literature. Methods A web-based, anonymous, and voluntary cross-sectional survey was developed and administered to Italian physiotherapists to evaluate their clinical practices. Results A total of 501 physiotherapists (38.5% female), completed the survey. More than half were under 35 years old (67.8%), declared working in private practice settings or being self-employed (57.1%), and were primarily engaged with musculoskeletal patients (81.8%). For subjects with FS at their first access, 21.4% identified X-rays as the most useful imaging technique to recognize pathologies beyond rehabilitation competence. In terms of general management, the majority reported working with an orthopaedic or physiatrist (47.5%) or in a multidisciplinary team (33.5%). Regarding manual therapy techniques, 63.3% of physiotherapists preferred intense degree mobilization, posterior direction, and moderate pain at the end of the range of motion for low irritable/high stiffness FS; however, there is a lack of consensus for managing very irritable/low stiffness FS. The majority of physiotherapists (57.7%) concurred that stretching improves the balance between metalloproteinase and its inhibitors. Additionally, 48.3% of physiotherapists selected mobile phone videos and messages to improve patients’ compliance with exercises at home and for motivational/educational purposes. Discussion and Conclusion The clinical practices of Italian physiotherapists in FS subjects sometimes deviate from evidence-based recommendations. While some discrepancies may be attributed to the existing uncertainties in the literature regarding knowledge and management strategies for FS patients, the authors recommend a stronger adherence to evidence-based practice.